FORMATION OF INNOVATIVE-INVESTMENT APPROACH IN MANAGEMENT OF FOREIGN ECONOMIC ACTIVITY OF TRANSPORT INDUSTRY COMPANIES - PLYASKINA АLONA; OHORODNYK, RYSLAN; OHORODNYK, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ukraine is currently at the stage of formation and consolidation of the industry, significantly inferior to Western European countries in terms of both quality and complexity of services provided by national transport companies. BSC (Balanced Score-Card) is not only an evaluation system, but also serves as a means of strategic management, as it allows you to formulate a strategy for the development of the company, and translate it into the plane of specific strategic objectives and indicators that determine them. The component of internal business processes determines the activities that are most important for achieving the goals of consumers and shareholders. The goals and indicators of this component are formed after the development of financial and customer components, which allows you to focus the parameters of internal business processes on the satisfaction of customers and shareholders.